Herondas por Herondas: autoficción en el mimo helenístico - Fernández, Claudia Nélida (2006)
In order to explore the writer's image inscribed in Herondas's work, this paper examines metafictional passages - mostly those of mimes VIII, IV and VI - that reveal how Herondas not only constructs his poetic voice but also takes control of the relationship with his audience, and furthermore, reveals his expectations concerning how he should be read. Such passages induce a rethinking of who were the historic receptors of these little Hellenistic dramas.